Morphogenesis of larval Onchocerca volvulus in the Panamanian black fly, Simulium quadrivittatum - Schiller, E.L; Petersen, J.L; Shirazian, D; Figueroa Marroquin, H (The American journal of tropical medicine and hygiene, 1984)
Simulium quadrivittatum Loew (Diptera: Simuliidae), a man-biting black fly, was shown, for the first time, to be capable of supporting development of Onchocerca volvulus Leuckart (Nematoda: Filarioidea) from microfilariae to third-stage (infective) larvae. The black flies were collected in Chiriqui Province, Panama and transported alive to Guatemala, where they were allowed to feed on a human subject infected with O. volvulus. Samples of these flies were dissected over an 11-day period to assess morphogenesis of the parasite. Vigorously motile microfilariae were recovered from the mid-gut during the first 24 hours postfeeding; second-stage larvae were found in the thoracic musculature on day 4; and fully developed third-stage larvae were obtained from the cephalic capsule by day 10. This rate of larval development is similar to that observed in Guatemalan S. ochraceum. Onchocerciasis is not known to occur in Panama. The results of the present study direct attention to a potential public health hazard there and possibly elsewhere in Central America.